Efficient enzyme‐free isolation of brain‐derived extracellular vesicles - Andreu Matamoros‐Angles; Emina Karadjuzovic; Behnam Mohammadi; Feizhi Song; Santra Brenna; Susanne Caroline Meister; Bente Siebels; Hannah Voß; Carolin Seuring; Isidre Ferrer; Hartmut Schlüter; Matthias Kneussel; et al. (Journal of Extracellular Vesicles)
Abstract Extracellular vesicles (EVs) have gained significant attention as pathology mediators and potential diagnostic tools for neurodegenerative diseases. However, isolation of brain‐derived EVs (BDEVs) from tissue remains challenging, often involving enzymatic digestion steps that may compromise the integrity of EV proteins and overall functionality. Here, we describe that collagenase digestion, commonly used for BDEV isolation, produces undesired protein cleavage of EV‐associated proteins in brain tissue homogenates and cell‐derived EVs. In order to avoid this effect, we studied the possibility of isolating BDEVs with a reduced amount of collagenase or without any protease. Characterization of the isolated BDEVs from mouse and human samples (both female and male) revealed their characteristic morphology and size distribution with both approaches. However, we show that even minor enzymatic digestion induces ‘artificial’ proteolytic processing in key BDEV markers, such as Flotillin‐1, CD81, and the cellular prion protein (PrPC), whereas avoiding enzymatic treatment completely preserves their integrity. We found no major differences in mRNA and protein content between non‐enzymatically and enzymatically isolated BDEVs, suggesting that the same BDEV populations are purified with both approaches. Intriguingly, the lack of Golgi marker GM130 signal, often referred to as contamination indicator (or negative marker) in EV preparations, seems to result from enzymatic digestion rather than from its actual absence in BDEV samples. Overall, we show that non‐enzymatic isolation of EVs from brain tissue is possible and avoids artificial pruning of proteins while achieving an overall high BDEV yield and purity. This protocol will help to understand the functions of BDEV and their associated proteins in a near‐physiological setting, thus opening new research approaches.